Overexpression of wheat ferritin gene TaFER-5B enhances tolerance to heat stress and other abiotic stresses associated with the ROS scavenging. Issue 1 (December 2017) - Zang, Xinshan; Geng, Xiaoli; Wang, Fei; Liu, Zhenshan; Zhang, Liyuan; Zhao, Yue; Tian, Xuejun; Ni, Zhongfu; Yao, Yingyin; Xin, Mingming; Hu, Zhaorong; Sun, Qixin; et al.
Abstract Background The yield of wheat (Triticum aestivum L.), an important crop, is adversely affected by heat stress in many regions of the world. However, the molecular mechanisms underlying thermotolerance are largely unknown. Results A novel ferritin gene, TaFER, was identified from our previous heat stress-responsive transcriptome analysis of a heat-tolerant wheat cultivar (TAM107).TaFER was mapped to chromosome 5B and namedTaFER-5B . Expression pattern analysis revealed thatTaFER-5B was induced by heat, polyethylene glycol (PEG), H2 O2 and Fe-ethylenediaminedi(o-hydroxyphenylacetic) acid (Fe-EDDHA). To confirm the function ofTaFER-5B in wheat, TaFER-5B was transformed into the wheat cultivar Jimai5265 (JM5265), and the transgenic plants exhibited enhanced thermotolerance. To examine whether the function of ferritin from mono- and dico-species is conserved, TaFER-5B was transformed intoArabidopsis, and overexpression ofTaFER-5B functionally complemented the heat stress-sensitive phenotype of a ferritin-lacking mutant ofArabidopsis . Moreover, TaFER-5B is essential for protecting cells against heat stress associated with protecting cells against ROS. In addition, TaFER-5B overexpression also enhanced drought, oxidative and excess iron stress tolerance associated with the ROS scavenging. Finally, TaFER-5B transgenicArabidopsis and wheat plants exhibited improved leaf iron content. Conclusions Our results suggest thatTaFER-5B plays an important role in enhancing tolerance to heat stress and other abiotic stresses associated with the ROS scavenging.